Implementasi Konsep Fasad dan Bentuk Arsitektur Kinetik pada Desain Sirkuit Balap Motor Nasional di Kepulauan Selayar - Firman, Firman; Marwati, Marwati; Alfiah, Alfiah (TIMPALAJA : Architecture Student Journals, 2025)
The Selayar Islands in South Sulawesi exhibit a strong love for the automotive realm, particularly motorcycle racing, engaging individuals of diverse age groups. The significant incidence of traffic accidents—120 instances in 2018 resulting in 8 fatalities and 37 occurrences with 3 fatalities in the first quarter of 2019—constitutes a grave concern, especially given that yearly motorcycle racing events utilise public roads as circuits in the Benteng area. This study seeks to construct a national-scale motorcycle racing circuit facility to mitigate unlawful street racing, decrease traffic accidents, promote local youth engagement in motorcycle racing, and boost tourism. The methods employed encompass literature evaluation, local requirement assessment, field surveys, and the development of design concepts that emphasise both functional and aesthetic dimensions, particularly the integration of dynamic facades as a pivotal architectural feature. The findings suggest that a motorcycle racing circuit, including a kinetic façade design, can offer a secure and standardised sports facility, diminish accidents resulting from illicit racing, foster local talent development, and markedly enhance tourism appeal in the Selayar Islands.